Lifelong medical challenges and immunogenetics of Turner syndrome - Won Kyoung Cho (Clinical and Experimental Pediatrics)
Turner syndrome (TS) is a female phenotypic condition characterized by one or more typical clinical features and the partial or complete absence of a second X chromosome as determined by karyotype analysis. TS, among the most common chromosomal abnormalities, has an estimated prevalence of approximately 1 in 2,500 live-born females, with ethnic and racial differences. TS encompasses a wide array of medical challenges, including cardiovascular, endocrine, autoimmune, and mental health issues, as well as a heightened cancer risk. The somatic stigmata of TS are thought to arise from haploinsufficiency of the X chromosomes. This review explores the lifelong medical challenges and immunogenetics of individuals with TS and aimed to investigate strategies for preventing and managing TS while considering the implications of immunogenetics.